ANALISIS KEBUTUHAN KARTU KANBAN PADA PROSES PERAKITAN PRODUK X - Yusnia Sinambela (Universitas Quality, 2020)
The kanban system is an information system that harmoniously controls the production of the required product in the required quantity at the time required in each manufacturing process and also between companies. CV X is a small-scale industry that produces assembled products. In this study, the focus is on the process of making earbuds which consists of three work centers, namely the activities of making Power Supply, installing Speaker Kits and Installing Speakers. This product is the product that is the most in order, demand over thousands for a month. The purpose of this research is to provide information on picking and transport, providing production information, preventing overproduction or overloading, acting as orders that are attached directly to components, preventing defective products by recognizing processes that create defects and disclosing existing problems and maintaining stock control. Based on the calculation, the number of kanban cards needed by work center I is 1,439, work center II is 1,165, work center III is 1,189, so the total required kanban card is 3,793 pieces